Toward an empathetic understanding of scholarship - Cox, Dana Christine (2019)
In this paper I take an autobiographical stance on knowledge production in the field of Mathematics Education, acknowledging forms of academic and racial privilege. I use my experiences as a backdrop by which to project a more empathetic approach to scholarship in mathematics education. Using the framework of rough draft thinking (JANSEN et al., 2015), I expose the contradictions in what we believe to be true about the acquisition and generation of mathematical and pedagogical knowledge, and the structures of scholarship in mathematics education. I make three recommendations: 1. address the need for rough draft spaces within the existing structure of academia; 2. we should reimagine our roles within the peer-review system; and 3. we need to adopt more empathetic methodologies that allow human voices to be centered in our scholarship without reduction or interpretation. It is no longer acceptable to believe that the gaze and interpretation of an objective researcher is as valid as the first-hand perspective of participants.